2014
DOI: 10.1021/bi5011877
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Studies of the Salmonella enterica Adenosyltransferase Enzyme SeCobA: Molecular-Level Insight into the Mechanism of Substrate Cob(II)alamin Activation

Abstract: CobA from Salmonella enterica (SeCobA) is a member of the family of ATP:Co(I)rrinoid adenosyltransferase (ACAT) enzymes that participate in the biosynthesis of adenosylcobalamin by catalyzing the transfer of the adenosyl group from an ATP molecule to a reactive Co(I)rrinoid species transiently generated in the enzyme active site. This reaction is thermodynamically challenging, as the reduction potential of the Co(II)rrinoid precursor in solution is far more negative than that of available reducing agents in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 64 publications
(167 reference statements)
2
36
0
Order By: Relevance
“…The 5c→4c Co(II)Cbl conversion yield achieved by EutT WT /Fe in the presence of excess MgATP largely exceeds the conversion yields reported for Se CobA and Lr PduO under similar conditions (~8% and 40% respectively). 38,39 …”
Section: Resultsmentioning
confidence: 99%
“…The 5c→4c Co(II)Cbl conversion yield achieved by EutT WT /Fe in the presence of excess MgATP largely exceeds the conversion yields reported for Se CobA and Lr PduO under similar conditions (~8% and 40% respectively). 38,39 …”
Section: Resultsmentioning
confidence: 99%
“…Previously, the mechanisms by which the CobA-type ACAT from Salmonella enterica , 31,32 the PduO-type human ACAT, 33 Lr PduO, 34 and the EutT-type ACAT from Salmonella enterica 35,36 can overcome the thermodynamically challenging Co(II) → Co(I)rrinoid reduction were investigated using magnetic circular dichroism (MCD) and electron paramagnetic resonance (EPR) spectroscopies. These studies led to the proposal that the ACAT/ATP complexes convert Co(II)rrinoids to effectively four-coordinate, square-planar species, thereby stabilizing the redox-active Co 3d z 2 -based molecular orbital (MO) and raising the reduction potential into the physiologically accessible range.…”
Section: Introductionmentioning
confidence: 99%
“…These features (referred to as the δ-, λ-, and σ-bands, respectively) are characteristic of 4c Co(II)Cbl. 17 However, several additional weak MCD features are observed on the high-energy side of the δ-band that have no counterparts in the MCD spectra of other 4c Co(II)rrinoid species. These features are attributed to the high spin Co(II) center that is present in EutT WT /Co ( vide infra ).…”
Section: Resultsmentioning
confidence: 99%
“…In support of this proposal, it has been shown that amino acid substitutions in the active sites of the CobA- and PduO-type ACATs aimed at altering the relative positioning of the two substrates could cause a significant decrease in catalytic activity, despite the fact that the variants retained the ability to generate sizable amounts of 4c Co(II)Cbl. 16,17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation